Avaliação da lordose cervical e da postura da cabeça em pacientes classe III esquelética submetidos à cirurgia ortognática - Andriola, Fernando de Oliveira (2018)
The purpose of this study was to evaluate cervical lordosis and head posture changes using lateral cephalographs after bimaxillary orthognathic surgery for mandibular prognatism by null hypothesis. Twenty-five patients with skeletal class III dentofacial deformities (10 men, 15 women; mean age, 29.28 ± 8.22 years; range 18-48 years) were included in this prospective clinical study. Lateral cephalographs were taken in natural head position (NHP) 2 weeks before and 6 months after orthognathic surgery. The reproducibility of the radiographer’s technique of taking radiographs in NHP was investigated using a photographic method and found to be acceptable. All measurements for cervical lordosis (CV1/CV2; CV3/CV7; CV1/CV7), head posture (NSL/OPT; NSL/VER) and other cephalometric values (NSL/Go-Gn; NSL/Ocl; Overjet) were repeated three times by the same investigator at 2- week intervals and the average values of the three measurements were calculated to use in statistical analysis. Intraclass correlation coefficients (ICC) ranged between 0.996 to 1.000, demonstrating a high reliability of the measures. Statistically significant differences were found for CV3/CV7 (P=0.006) and CV1/CV7 (P=0.005) and no significant differences were identified in head posture for both cranio-cervical and cranio-vertical angles. The null hypothesis was rejected. Orthognathic surgery resulted in significant cervical lordosis extension, and a tendency for head extension could also be observed.